Intraosseous epidermoid cyst of distal phalanx—Report of two cases - Dong Hwan Kim; Jung Ho Noh (Clinical Case Reports, 2023)
Key Clinical Message Intraosseous epidermoid cysts in this report were related to a previous injury. A careful history taking is necessary to make a correct impression on the lesion. Definite diagnosis is made by histologic study. Abstract This report presents two cases of intraosseous epidermoid cyst of the finger treated with curettage and autogenous bone graft. Radiographs showed a radiolucent lesion with a sclerotic margin. Histologic examination revealed a cystic wall consisting of stratified squamous epithelial cells and keratinized material in the cyst, consistent with an epidermoid cyst.